Support network, oral health quality of life and social support during pregnancy: a cross study - Brasileiro, Francisca Marília Cruz (2024)
A support network (SN) during pregnancy is essential. The SN can be the partner, a family member or someone from the social circle directly involved in caring for the pregnant woman. During pregnancy, the SN plays a crucial role in health promotion. The study aimed to identify the pregnant woman\'s SN and assess its relevance to perceived social support and quality of life. This study was conducted with 95 pregnant women living in Ribeirão Preto (São Paulo, Brazil), treated within the Unified Health System (SUS). SN during pregnancy was measured by Social Support Scale (MOS-SSS) questionnaire and classified as \"High\" and \"Medium and Low\" categories. Qualify of life was measured using the Oral Health Index Profile (OHIP-14). Statistical analysis was performed using Chi-square test with Yates\' correction or Fisher\'s exact test, with \"best models\" in which at least one independent variable obtained a p-value<0.05 and a 95% confidence interval. Pregnant women whose main SN was \"Family\" showed higher perception of \"Material support\" compared to those whose main SN was the \"Partner\" (p=0.005). The \"Disability\" domain of OHIP-14 was associated with perceptions of \"Material support\" (p=0.026), \"Emotional/informational support\" (p=0.014), and \"Social interaction\" (p=0.001). There was also an association between having a companion at appointments and the perception of \"Emotional/informational support\" (p=0.021). Our study showed that pregnant women with a higher prevalence of \"Emotional/informational support\" had the presence of the SN at prenatal consultations. Also, having the SN composed of a family member was more prevalent among those with a high perception of \"Material support\". About the oral health-related quality of life domains \"Functional limitation\" and \"Inability\" were more prevalent in pregnant women who had \"medium and low\" perceptions of social support in the \"Material support\" and \"Social interaction\" scores.